Isolation of fungi causing rot of cocoyam (colocasia esculenta (l.) schott) and control with plant extracts: (allium sativum, l., garcinia kola, heckel., azadirachta indica, l. and carica papaya, l.) - Anukworji C A; Ramesh .R.Putheti; R. N. Okigbo (Global Journal of Food and Agribusiness Management, 2020)
Antifungal effect of aqueous and ethanol extracts of Allium sativum, Azadirachta indica, Carica papaya and Garcinia kola on the growth of fungal pathogen of stored cocoyam cormels were investigated invitro. Four different extract concentrations were obtained from each plant parts used by blending 25g, 50g, 75g and 100g in 100ml of sterile distilled water (SDW). Phytochemical screening of the plants was conducted using different standard methods; this revealed the presence of alkaloid, saponin, tannins, flavonoid, phytate, oxalate and phenol in all the plants but at different concentrations. Effect of standard antibiotics (Grisovid) comparative to the plant extracts was determined. Pathogenicity test revealed that Aspergillus niger, Fusarium solani, Sclerotia rolfsii and Botryodiplodia theobromae induced rot in healthy cocoyam cormels after 6 days of inoculation with Botryodiplodia theobromae being the most virulent. Even though all the extracts showed varying degrees of antifungal efficacy, ethanol extract proved to be more potent. The efficacy of the extract varied with the solvent of extraction, extract concentration and the test pathogens. Inhibition of fungal growth increased with a corresponding increase in extract concentration. Allium sativum and Azadirachta indica depicted an effective/high rate of inhibition on the mycelia growth of all the test fungi ranging from 40.57% to 92.40% whereas, extract of Carica papaya and Garcinia kola showed a lower inhibition rate ranging from 0.0% to 60.17%. 10% extract concentration of Allium sativum and Azadirachta indica being the most fungitoxic showed a significant (P<0.05) inhibition on all the test fungi pathogens. The fungitoxic potential of these plant extracts on rot inducing fungi of stored cocoyam corms/cormels recommends their use to farmers as alternative to commercial / synthetic fungicides.